An IoT-based cognitive impairment detection device: A newly proposed method in older adults care—choice reaction time-device development and data-driven validation - Vizitiu, Cristian; Stara, Vera; Antognoli, Luca; Dinculescu, Adrian; Mosoi, Adrian; Kristaly, Dominic M.; Nistorescu, Alexandru; Rampioni, Margherita; Dominey, Kevin; Marin, Mihaela; Rossi, Lorena; Moraru, Sorin-Aurel; et al. (SAGE Publications, 2024)
Background Research shows that older adults' performance on choice reaction time (CRT) tests can predict cognitive decline. A simple CRT tool could help detect mild cognitive impairment (MCI) and preclinical dementia, allowing for further stratification of cognitive disorders on-site or via telemedicine. Objective The primary objective was to develop a CRT testing device and protocol to differentiate between two cognitive impairment categories: (a) subjective cognitive decline (SCD) and non-amnestic mild cognitive impairment (na-MCI), and (b) amnestic mild cognitive impairment (a-MCI) and multiple-domain a-MCI (a-MCI-MD). Methods A pilot study in Italy and Romania with 35 older adults (ages 61–85) assessed cognitive function using the Mini-Mental State Examination (MMSE) and a CRT color response task. Reaction time, accuracy, and demographics were recorded, and machine learning classifiers analyzed performance differences to predict preclinical dementia and screen for mild cognitive deficits. Results Moderate correlations were found between the MMSE score and both mean reaction time and mean accuracy rate. There was a significant difference between the two groups’ reaction time for blue light, but not for any other colors or for mean accuracy rate. SVM and RUSBoosted trees were found to have the best preclinical dementia prediction capabilities among the tested classifier algorithms, both presenting an accuracy rate of 77.1%. Conclusions CRT testing with machine learning effectively differentiates cognitive capacities in older adults, facilitating early diagnosis and stratification of neurocognitive diseases and can also identify impairments from stressors like dehydration and sleep deprivation. This study highlights the potential of portable CRT devices for monitoring cognitive function, including SCD and MCI.